Analisis Tata Letak Fasilitas PT Mandiri Banana Indonesia dengan Mengaplikasikan Metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Eka Yudha Firmansyah; Rizki Okina Putri; Irawati Lukman; Fazar Hidayatulloh; Alifa Fauzia Siswoyo; Khoirul Aziz Husyairi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
PT Mandiri Banana Indonesia still requires further development and arrangement of its layout and facilities to enhance the efficient and optimal use of land. This study aims to determine whether the existing layout at PT Mandiri Banana Indonesia is effective in supporting operational flow and the uninterrupted progression of the production process. The research adopts a quantitative descriptive approach, which is used to measure the correlation between activities through the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. These methods enable the analysis to be presented in a measurable and objective manner as a basis for improving the facility layout. This study proposes a new layout design for the main production area and supporting facilities. The proposed layout is based on the results of ARC and TCR analyses, which indicate several critical spatial interrelationships among the facilities. Based on the findings and discussion regarding the application of the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) in designing the facility layout at PT Mandiri Banana Indonesia, it may be inferred that layout improvement exerts a significant impact on enhancing workflow efficiency and the overall work environment. The proposed alternative layout is expected to achieve a safer, more hygienic, and more productive spatial arrangement by establishing a clear separation between the production zone, administrative zone, and supporting areas.